Implementasi Pembelajaran Berdiferensiasi Dalam Kurikulum Merdeka Belajar Pada Pembelajaran Ekonomi di SMA Negeri 2 Jember - Dwi Novita Lissa Putri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study was conducted to describe and analyze the implementation of differentiated learning in the kurikulum merdeka belajar in economics learning at SMA Negeri 2 Jember. The data collection methods used were interview, observation and document methods. The main informant in this study was the Economics subject teacher of class X at SMA Negeri 2 Jember and the supporting informant was the students of class X9 at SMA Negeri 2 Jember. This study is a descriptive study with qualitative research, namely presenting data obtained by researchers from the results of interviews, observations, and documents that have been obtained. The results of this study indicate that the implementation of the differentiated learning model in the kurikulum merdeka belajar in economics learning at SMA Negeri 2 Jember has been carried out by economics subject teachers in class X by conducting diagnostic assessment tests or student mapping, after which the preparation stage was carried out with the role of the teacher as a designer, facilitator and motivator. Furthermore, the teacher implements differentiated learning in the classroom, the teacher implements the implementation of process differentiation, the teacher divides 36 students into 6 groups. Each group has been given LKPD that discusses the basic material of economics after that the teacher asks students to have a group discussion with the learning style and interests that suit the students. After conducting the discussion, the teacher gives a formative test in the form of a descriptive test of 10 questions. The implementation of differentiated learning has advantages, it can increase student motivation and learning outcomes such as helping students understand better, making the classroom atmosphere more comfortable and enjoyable, helping teachers achieve learning outcomes. The disadvantages of implementing differentiated learning require sufficient resources such as time, space, and teaching materials, effective classroom management skills
Reaploud Repository April 2026
Keywords: Differentiated Learning; kurikulum merdeka; Economics Subject